A different method to accelerate orthodontic tooth movement: Randomized controlled trial - Yildiz Osman; Yagci Ahmet; Hashimli Nizami (Balkan Stomatological Society, 2023)
Background/Aim: Since both patients and orthodontists want orthodontic treatment to be completed in a short time, various methods have been developed to accelerate orthodontic tooth movement. Vibration applications and interrupted force are noninvasive applications that are easily accepted by the patient. Aim of this study is researching modified interrupted force and vibration together how effect orthodontic tooth movement rate and pain perception that occurs during canine distalization. Material and Methods: Twenty patients (10 males and 10 females) with Class II div 1 malocclusion were selected for this study. The Hycon device on the right side activated by routine protocol, but on the left side activation protocol modified. The patients were randomly divided into 2 groups and one group was applied vibration with AcceleDent device. Each patient was provided with a chart to score the pain they experienced during canine distalization. Results: Fastest tooth movement was measured in the modified protocol(HL)+AcceleDent group (1.44 mm/monthly). The results showed that the orthodontic tooth movement in the groups which AcceleDent device used was faster than the Hycon groups only. Faster movement was observed in the left canines which Hycon device activated by modified protocol compared to right canines. These differences between groups were found statistically significant. Pain over time exhibited similar patterns in all groups. Conclusions: Using modified interrupted force protocol gave more rapid extraction space closure. The application of vibration, as an adjunct to treatment with a fixed orthodontic appliance, significantly increases the rate of orthodontic tooth movement. Vibrational force and modified activation protocol do not have significant effect on pain perception.